(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aims to identify the reality of digital citizenship among Sudanese students in Egyptian universities and contemporary challenges. The researcher applied the descriptive approach to a sample of Sudanese students in Egyptian universities. The study concluded with many results, the most notable of which are: Individuals of the sample believe that the motives for their exposure to digital devices and modern technologies are: It enjoys ease of browsing, followed by exchanging experiences and information with others at a rate of 77.7%, While 81.6% confirmed that they trust to some extent what is displayed on digital devices, and 68.9% interact to a moderate degree with what is shown through them.